Update on optimal treatment for metastatic colorectal cancer from the ACTG/AGITG expert meeting: ECCO 2015. Issue 5 (3rd May 2016) - Price, Timothy J; Thavaneswaran, Subotheni; Burge, Matthew; Segelov, Eva; Haller, Daniel G; Punt, Cornelis JA; Arnold, Dirk; Karapetis, Christos S; Tebbutt, Niall C; Pavlakis, Nick; Gibbs, Peter; Shapiro, Jeremy D
ABSTRACT: The treatment of metastatic CRC (mCRC) has evolved over the last 20 years, from fluoropyrimidines alone to combination chemotherapy and new biologic agents. Median overall survival is now over 24 months for RAS mutated (MT) patients and over 30 months for RAS wild-type (WT) patients. However, there are subgroups of patients with BRAF V600E MT CRC who have a significantly poorer outlook. Newer treatment options are also being explored in select subgroups of patients (anti-HER 2 in HER2 positive mCRC and immunotherapy in patients with defective mismatch repair (dMMR)). The best use of these systemic treatment options, as well as surgery in well-selected patients requires careful consideration of predictive biomarkers and importantly, the optimal sequence in which therapies should be given to derive maximal benefit. A group of colorectal subspecialty medical oncologists from Australia, USA, The Netherlands and Germany met during ECCO 2015 in Vienna to review current practice.